Love at the core - the phenomena of love in the therapeutic relationship in nursing - Patrícia Silva Pereira; Maria Antónia Rebelo Botelho (Nursing Research, Innovation and Development Centre of Lisbon (CIDNUR) of the Nursing School of Lisbon (ESEL), 2021)
Love is a small word that carries many meanings. In everyday life, we refer to love without considering its meaning because the meaning depends on the object to which we refer. Love in nursing is considered one of the pillars of the science of caring. However, this assumption has some misunderstandings. It is important to clarify the scope of love in a therapeutic relationship and to understand how love manifests itself. Objective: To understand the lived experience of love by mental health nurses in the therapeutic relationship in nursing. Method: The study used a qualitative methodology, phenomenology of practice established by Max van Manen, rooted in philosophy, using philosophical, philological, and human sciences methods. Experiential reports were collected from 10 mental health nurses. The understanding of the meanings and senses of the phenomenon was based on radical reflection using epoché and reduction. Results: Love shows itself as seeing the invisible; as the impossibility of non-action; as reassuring gestures; as "going the extra mile"; as being attuned; as being connected; as letting the other to emerge; as hosting the other in oneself; as a pathic experience; and as a personal cost. Conclusion: Love is a transformative ingredient of the therapeutic relationship experience. This study is a possible understanding of the phenomenon of love in the therapeutic relationship in nursing. In addition, the study is a contribution to help clarify and demystify stereotypes and trigger reflections on the everyday relationships in nursing. Therefore, it may promote understandings that make the practice of care more sensitive and closer to the world of each patient.